Impact of Climate Change on Macro-Economy of Central Sulawesi Province Indonesia: Case of Cocoa Beans Commodity - M.R. Yantu; Yulianti Kalaba; Arifuddin Lamusa; Wildani Pingkan S. Hamzens (Universitas Tadulako, 2015)
Central Sulawesi is the first rank of cocoa beans supplier in Indonesia. Unfortunately, climate change resulted on emerging of cacao pests and diseases that causes continuously decreasing productivity of cacao farm. Consequently, farmers have been converted their cocoa farm to others farm. This has been impacted on macro-economy of Central Sulawesi. Generally, the aim of this study is to analyze impact of climate change on macro-economy of Central Sulawesi for case cocoa beans commodity. Particularly, the aim of this study is (i) to analyze impact of climate change on productivity of cacao farm; (ii) to estimate effect of the productivity on GDRP of cocoa beans; (iii) to estimate effect of the GDRP of cocoa beans on macro-economy of Central Sulawesi; and (iv) to estimate trends of macro-economy of Central Sulawesi. Analyze method was econometric simultaneous equation of double logarithm model. Data used was secondary data, 2000 – 2014, namely GDRP of Central Sulawesi, areal size of cacao, production volume of cocoa beans, prices of cocoa beans at farm level. The result of analyze showed that climate change has been impacted on productivity of cacao farm. It was indicated by coefficient of year as a proxy insignificant affect to variety of productivity of cacao farm, so it could be interpreted that the productivity to be constant. Consequently, the productivity couldn’t push up GDRP of cocoa beans. However, GDRP of cocoa beans could still push up the macro-economy of Central Sulawesi. The macro-economy of Central Sulawesi was increasing. Thus, although climate change impacted on the productivity, but GDRP of cocoa beans could still push up the macro-economy of Central Sulawesi. It means that management of pest and disease of cacao farm in a prototype to be important performed.